COMMUNICATION STRATEGY OF LAZISWAF IN INCREASING FUNDRAISING CHARITY AT MAIN CAMPUS SIMAN - buyung nugra askiya' (Sahafa Journal of Islamic Communication, 2021)
This study focuses on examining how LAZISWAF's in increasing fundraising charity is to attract the interest of target donors in giving charity.This research was carried out at the LAZISWAF office, Siman Central campus, the main building, 2nd floor, Siman Campus, Darussalam University (UNIDA). The research method uses a descriptive qualitative approach in the form of words, written, or oral from informants and data from LAZISWAF as a form of credibility.The results showed that LAZISWAF's communication strategy to attract target donors' interest in giving charity consisted of four indicators, namely, (1) selecting and assigning communicators; (2) determine the audience; (3) message composing techniques; (4) select media . Analyzed based on data obtained in the field using the communication formula theory of Hafied Cangara. In addition to this, LAZISWAF communicators must have the power to attract target donors at UNIDA using French and Raven theory (critical resources) which are proven to be efficient. Prospective muzakki or target donors can easily get information about the importance of paying zakat and LAZISWAF is more concerned with delivering messages with powers, including, (1) coercive power; (2) Expert power (expert power); (3) Informational Power; (4) Referent Power; and (5) Legitimate Power.